Pengaruh Self Confidence dan Self Efficacy terhadap Kemampuan Berpikir Kreatif Matematika Siswa SMP - Anita Sabrina Pasaribu; Firman Pangaribuan; Hardi Tambunan (Departement of Mathematics Education, 2024)
On the achievement of mathematical creative thinking, an important aspect that must be possessed by students is self confidence and self efficacy is good, because in self confidence and self efficacy there are indicators that can supportthat goal. This studyaimsto find out indepth about the influence of self confidence and self efficacy simultaneously to the ability of mathematical creative thinking of junior high school students. The population in this study were junior high school students in Kabupaten Simalungun. Instrument in this research in the form of test of creative thinking ability of mathematic counted four problem, and enquette self confidence and self efficacy student. Methods in this study using multiple regression method. The results of this study indicate that there is influence of self confidence and self efficacy to the ability of mathematical creative thinking of junior high school students.